Stranger in the Shogun's city : a Japanese woman and her world - Stanley, Amy, 1978- (Scribner, 2020)
"A vivid, deeply researched work of history that explores the life of an unconventional woman during the first half of the 19th century in Edo-the city that would become Tokyo-and a portrait of a great city on the brink of a momentous encounter with the West."--